Chemical, mineralogical, and physicochemical features of surface saline muds from Southwestern sub-basin of the East Vietnam Sea: Implication for new peloids - Le Duc, Luong; Nguyen, Hoang; Shinjo, Ryuichi; B. Shakirov, Renat; Obzhirov, Anatoly (Vietnam Journal of Earth Sciences, 2021)
This study presents the chemical, mineralogical and physicochemical features of 8 saline mud samples from 8 gravity cores located in the southwestern sub-basin of the East Vietnam Sea. The grain-size analysis of mud samples reveals the amount of clay and silt particles in the ranges of 65.1-89.2% and 9.5-34.2%, respectively and a very low fraction of sand. The analytical results showed that mud samples have high contents of SiO2 (32.79-48.09%), Al2O3 (11.26-13.63%), CaO (3.10-13.93%), Fe2O3 (4.15-9.45%), and low contents of TiO2, MnO, MgO, Na2O, K2O and P2O5. The XRD analysis of mud samples indicated mineral compositions with major minerals of quartz, illite, calcite, chlorite, feldspar, kaolinite, and other minor minerals like halite, smectite, fluorapatite, pyroxene, amphibole. The organic and physicochemical parameters of mud samples were also measured. Potentially toxic elements in mud samples were determined and compared with reference values and the technical standard. This study proposes that saline mud samples from the studied area are potential peloids.